Employee Advocacy : Strategi Branding Kontemporer dalam Membangun Brand Image - Resya Nur Intan Putri; Ulfah Rosyidah; Almira Yoshe Alodia (Fakultas Ilmu Sosial Dan Politik, Universitas Wijayakusuma Purwokerto, 2025)
The advancement of digital technology has driven organizations to integrate communication strategies that engage employees as agents in shaping the company’s image and reputation. This study aims to analyze the role of Corporate Public Relations (PR) practitioners in promoting and managing employee advocacy in the digital era, using a case study of Java Heritage Hotel Purwokerto. A qualitative approach was employed through in-depth interviews with four informants exhibiting diverse levels of digital engagement, including activities on personal social media and participation in the company’s official content. The findings indicate that Corporate PR practitioners play a strategic role in fostering participatory internal communication and empowering employees to contribute to the development and dissemination of content that supports brand narratives. Employee advocacy manifested in two primary forms: (1) personal expressions shared by employees on their social media accounts, and (2) employee involvement as key figures in official content produced by the PR team. This phenomenon is exemplified by the active participation of individuals on their personal social media, and person who featured in official company content that attracted millions of viewers on TikTok. The findings align with strategic communication theories, including PR Excellence Theory, Networked Publics Theory, and Impression Management Theory. In addition to enhancing digital engagement, the employee advocacy strategy implemented by Java Heritage Hotel successfully strengthened the company’s image and reputation in the digital sphere. This study contributes theoretically by expanding the understanding of structured and managed models of employee advocacy and offers practical implications for the development of corporate communication strategies in the social media era.